Creating Shared Value through Coral Reef Transplantation Program: Membangun Nilai Bersama Melalui Program Transplantasi Terumbu Karang - Khoirulika , Rizka; Nurcahyo, Andik; Oktavia , Siska; Naibaho, Kampoi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Indonesia is one of the countries within the Coral Triangle region, known for its vast coral reef ecosystems that sustain marine biodiversity and coastal livelihoods. Specific background: In the Kangean Islands, East Java, coral reefs face significant degradation caused by destructive fishing practices and climate change. To address this, Kangean Energy Indonesia Ltd. (KEI), an upstream oil and gas company, initiated a coral reef transplantation program as part of its environmental commitment. Knowledge gap: Previous studies on corporate social responsibility (CSR) have rarely examined how the Creating Shared Value (CSV) approach can simultaneously promote ecological restoration and community welfare within the extractive industry. Aims: This research analyzes the implementation of CSV principles—shared value, community involvement, collaboration, and innovation—in KEI’s coral reef transplantation program. Results: Using a qualitative approach through interviews, observations, and document analysis, the study finds that CSV enhances coral ecosystem recovery, empowers youth, fosters cross-sector collaboration, and introduces dome-shaped transplantation media as an innovation. Novelty: The study offers a new model of CSV-based marine conservation integrating business sustainability with ecological and social outcomes. Implications: The findings highlight CSV’s potential as a strategic framework for the oil and gas sector to advance sustainable development and strengthen community legitimacy. Highlights: CSV links corporate sustainability with community and ecosystem welfare. Innovative dome-shaped media enhance coral restoration success. Multi-stakeholder collaboration ensures long-term social legitimacy. Keywords: Creating Shared Value, Coral Reef Transplantation, Community Involvement, Collaboration, Innovation